Analytical Prediction Model for Indoor Particle Deposition onto Ocular Surface. (June 2016) - Yang, Zhang; Nianping, Li; Chen, Wang; Jing, Zeng
Abstract: This paper was based on the definition of particle deposition velocity. By analysis the deposition mechanisms of particle in concentration boundary layer, the paper deduced an analytical expression of differential equation about dimensionless deposition velocity onto ocular surface. Then the paper adopted a series of reasonable approximation formula to simplify the expression of dimensionless deposition velocity. The rationality and the accuracy of the prediction model were verified by experimental data in a reference paper. It was testified that the deposition velocity onto the ocular surface firstly decreases and then increases with the increase of the particle diameters when under low friction velocity. The deposition velocity continuously increases with the increase of the particle diameters when under relatively high friction velocity. The model could contribute to low carbon city, energy conservation and emissions reduction in theory.